Exploring hidden topics on hotel Facebook fan pages before and during the COVID-19 crisis - Rabadán-Martín, Inmaculada; Aguado-Correa, Francisco; Padilla-Garrido, Nuria (Review of Business Management, 2023)
Purpose – This study analyzes the way that firm-generated content (FGC) was adapted in the accommodation sector through hotel chains’ Facebook posts at a time of crisis. Specifically, this research aims to: (1) explore hidden topics in hotel chains’ FGC; (2) classify topics according to their promotional or non-promotional content; and (3) compare topics during the first months of the COVID-19 crisis and the same months of 2019. Theoretical framework – The method/theoretical approach used in this research is social network analysis. Design/methodology/approach – We used content analysis to examine 1,317 Facebook posts from the five hotel chains with the greatest presence in Spain. NodeXL software was used to create a semantic network to reveal the relationships between the ideas embedded in the text collection. Findings – 14 latent topics were found in each period, including promotional and non-promotional content. Non-promotional topics increased from one third in 2019 to more than half in 2020, and the most relevant topic in 2020 was "Competitions." Practical & social implications of the research – The findings of our study suggest that during the pandemic, unlike other crises, hotel chains used Facebook to accompany users, entertain them, and maintain the emotional connection with the brand, responding to societal demands. Originality/value – This study is novel not only because of its focus on FGC in the tourist accommodation sector, but also because it uses semantic network analysis to study the way in which firms make use of social media in crisis situations. Keywords – content analysis, semantic network, firm-generated content, accommodation, tourism crisis.